Reliability of medium-range weather forecast for Jabalpur region of Madhya Pradesh - GUPTA, V K; AGRAWAL, K K; UPADHYAY, A P; SHANKER, UPENDRA (The Indian Journal of Agricultural Sciences, 2013)
For successful utilization in agricultural - decision making, medium - range weather forecasts of rainfall and the maximum and minimum temperatures during 1993 and 1994 for Jabalpur were validated and their reliability was assessed. The seasons for rainfall as well as temperature. The accuracy (%) was very high for occurrence of rainfall, although forecasting of rainfall amount needs substantial improvement. Actual temperatures also deviated from those forecast but this was probably due to local factors. Result indicated overall improvement in reliability factor forecasts for both the elements.